Numerical modeling and minimization of enclosure interior noise using local active sound control - Mohamady, Samira (2010)
Low frequency noise has detrimental effects on human’s physiology and psychology. To reduce low frequency noise, active control of sound is more effective compared to passive sound absorbers. Reduction of low frequency noise in structures like vehicle cabin and room in a house is therefore important. These structures can be modeled as a three dimensional (3D) enclosure with a flexible boundary structure on one of its side. In this thesis minimization of sound pressure in an enclosure with five rigid walls and a flexible plate on its top side using local active noise control technique was investigated. The acoustic environment of the enclosure was modeled using the finite element method. COMSOL© MULTIPHYSICS software which provides structural and acoustical modules was used to create finite element model of the enclosure. Modal analysis of this system was performed and the eigenfrequencies were compared against those obtained in related analytical and experimental works. In order to verify the finite element modeling procedure, convergence analysis of the system was performed. The eigenfrequencies of the finite element model were compared with the ones obtained for analytical and experimental models and the mean absolute error of 5.8 % and 4.3 % were achieved respectively. Local control method has been used to design the controller in reducing the interior sound pressure field at two observer locations. The estimated noise reduction was assessed by calculating the estimated sound potential energy in the enclosure with and without controller. An average of 140.4 dB reduction in estimate potential energy in low frequency range has been obtained. Reduction of sound pressure at each observer position is around 60 dB. This implies that local active control of sound can be used in reducing sound pressure level at desired observer locations within the enclosure.